The Effect of Consumer-based Activity Tracker Intervention on Physical Activity among Recent Retirees-An RCT Study - Leskinen Tuija; Suorsa Kristin; Tuominen Miika; Pulakka Anna; Pentti Jaana; Löyttyniemi Eliisa; Heinonen Ilkka; Vahtera Jussi; Stenholm Sari (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Purpose The randomized controlled trial REACT (NCT03320746) examined the effect of a 12-month consumer-based activity tracker intervention on accelerometer-measured physical activity among recent retirees.
Methods Altogether 231 recently retired Finnish adults (age, 65.2 +/- 1.1 yr, mean +/- SD; 83% women) were randomized to intervention and control groups.
Intervention participants were requested to wear a commercial wrist-worn activity tracker (Polar Loop 2; Polar, Kempele, Finland) for 12 months, to try to reach the daily activity goals shown on the tracker display, and to upload their activity data to a Web-based program every week. The control group received no intervention. Accelerometer-based outcome measurements of daily total, light physical activity (LPA), and moderate to vigorous (MVPA) physical activity were conducted at baseline and at 3-, 6-, and 12-month time points. Hierarchical linear mixed models were used to examine the differences between the groups over time. All analyses were performed by intention-to-treat principle and adjusted for wake wear time.
Results The use of a commercial activity tracker did not increase daily total activity, LPA, or MVPA over the 12-months period when compared with nonuser controls (group-time interaction, P = 0.39, 0.23, and 0.77, respectively). There was an increase in LPA over the first 6 months in both the intervention (26 min center dot d(-1), 95% confidence interval [CI] = 13 to 39) and the control (14 min center dot d(-1), 95% CI = 1 to 27) groups, but the difference between the groups was not significant (12 min center dot d(-1), 95% CI = -6 to 30). In both groups, LPA decreased from 6 to 12 months.
Conclusion The 12-month use of a commercial activity tracker does not appear to elicit significant changes in the daily total activity among a general population sample of recent retirees, thus highlighting the need to explore other alternatives to increase physical activity in this target group.